Hictorical Of Sufism In Recent Centuries - Rahmat Lutfi Guefara; Ali Mu’tafi; Robingun Suyud El Syam (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2023)
The emergence of research examining Islamic mysticism or Sufism in recent centuries, reaching its peak in the 20th century, indicates significant development of Sufism outside the Islamic world. This is evidenced by the presence of Muslim communities in the West who adhere to Sufi teachings. The aim of this article is to explore the development of Sufism in the West, focusing on two aspects: (1) Examining the theories and early studies on the introduction of Sufism to the West since the 17th century; (2) Investigating the models and patterns of Sufism that have emerged in the West, especially in the 20th century. This research employs a qualitative approach with methods of historical and philosophical analysis. The research findings include: (1) Western studies on Sufism began as early as the 17th century and reached their peak in the 19th/20th century, marked by numerous translations of Sufi texts. (2) In the 20th century, several models or patterns of understanding Sufism emerged in the Western world, namely hybrid, perennial, and transplant Sufism.